Perancangan Buku Saku Sebagai Bahan Ajar Mata Pelajaran Humas dan Keprotokolan Kelas XI OTKP 2 di SMKN 1 Bojonegoro - Coco Dwi Permana; Durinta Puspasari (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
A pocket book is a small sized book , practical and light that contains concise material or information and there are interesting pictures. Because the small size of the pocket book is easy to carry and can be read anywhere. This research aims to describe the process of development pocket books as teaching materials for Public Relations and Protocol class XI OTKP 2 SMKN 1 Bojonegoro. The development that will be used is 4D models development  from Thiagarajan which has been ajusted. The steps that will be done are definine, design, but for the  development and desseminate step will not be done because of the researcher's limitations. The results showed that the process of development a pocket book has several steps for the definition stage: 1) initial analysis which includes analysis initial abilities of students, concept analysis, task analysis and the formulation of learning objectives, 2) the design phase includes designing the material and initial design of the pocket book.